A Subtitling Analysis On Expressive Utterances On The Mirror Mirror Movie - Sejati, Wahyu Agung; , Dra. Dwi Haryanti, M.Hum; , Siti Fatimah, S.Pd, M.Hum (2013)
This research studies about the subtitling strategy analysis of expressive utterances in Mirror Mirror movie. The objectives of the study are to describe the kind of expressive utterances and to identify the types of subtitling strategies in its subtitle. This research applies descriptive qualitative research. By applying this method, the researcher uses the subtitle of Mirror Mirror movie as the data source, while the data of the research are expressive utterances. As the comparison, there are also data taken from manuscript in English and Indonesian. The method of collecting data is document and interviewing the viewers of the movie to get their opinion of the movie. The technique of analysis applied in this study is descriptive analysis. First, the results of the research show that 63 data of expressive utterances, the researcher finds seventeen kinds of expressive utterances, they are: happiness, apologizing, affront, dislike, proud, anger, disagreeing, threatening, hoping, thanking, permission, denying, afraid, pleasure, praise, requesting, and greeting. Second, from 63 data, the researcher finds 5 types of subtitling strategy, they are: 7 data or 11.1% translated using paraphrase, 46 data or 73.01% using transfer, 8 data or 12.7% using condensation, 1 data or 1.6% using decimilation, and 1 data or 1.6% using deletion.